Sejarah Peradaban Islam Masa Dinasti Umayyah (661-750 M) - Zuairiyah Zuairiyah; Fathiyah Husna; Nisrina Nisrina; Rona Sifaun Nada; Yuli Setyawati; Purnomo Purnomo (Gemi: Jurnal Penelitian dan Pengabdian, 2026)
The Umayyad Dynasty in Damascus marked the beginning of Islam’s shift from a democratic caliphate to a hereditary monarchy. This study aims to examine the history, civilizational advancements, and causes of the Umayyad Dynasty's decline in Damascus. The method used is library research, referring to historical texts, articles, and relevant academic sources. Findings reveal significant progress in politics, law, culture, economy, education, and religion during the dynasty’s rule. However, internal issues such as weak leadership, tribal fanaticism, and economic decline led to its fall. This research is crucial for understanding the dynamics of classical Islamic civilization and its relevance to the development of contemporary Islamic politics.